Anti-radiation aggregate, preparation method thereof and high-strength anti-crack anti-radiation concrete
By preparing high-density aggregate cores with irregular channels and combining the treatment of sodium alginate and boron fibers, a multi-layer structural aggregate is formed, which solves the problems of large self-weight and easy separation and stratification of existing radiation-proof concrete aggregates, and achieves efficient radiation energy absorption and improvement of concrete performance.
Patent Information
- Application Number
- CN202411880915.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-19
AI Technical Summary
While existing radiation-proof concrete improves radiation resistance, the aggregate is large in weight and the concrete is easy to be separated and layered, resulting in poor mechanical properties.
High-density aggregate cores with irregular pores are prepared using materials such as lead powder, iron ore powder and barium cement. Through the treatment of sodium alginate and boron fibers, a multi-layer structural aggregate is formed, combined with a red mud polymer encapsulation layer to enhance the density and strength of the aggregate.
The layer attenuation and absorption of radiation energy is achieved, the risk of separation of aggregate self-weight and concrete is reduced, and the working and mechanical properties of concrete are improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a radiation-proof aggregate and a preparation method thereof, and high-strength crack-resistant radiation-proof concrete. Background Art
[0002] With the development of the nuclear industry, nuclear technology is increasingly being used in energy, agriculture, military and medical fields. Nuclear facilities such as nuclear reactors and high-energy particle accelerators will produce strong penetrating rays during use. People who work in such an environment for a long time will be harmed by the rays, causing a decrease in human immunity. Therefore, when building buildings with radiation sources, shielding protection must be done well. Nuclear radiation generally includes α, β, γ, X and neutron rays, among which α, β and X rays have low transmission ability and are easily absorbed, and are not the main objects of protection. γ rays and neutron rays are the most important objects of protection in the field of radiation protection. γ rays are a high-energy, high-frequency electromagnetic wave composed of strong photon streams, with extremely strong penetrating ability. When shielding them, materials with large atomic numbers and high densities are generally used; neutron rays are also uncharged and have extremely strong penetrating power. Light elements have higher neutron absorption cross-sections, which can increase the probability of reaction with neutrons. Materials with more hydrogen elements are usually used as neutron absorbers.
[0003] As a radiation shielding material, radiation-proof concrete has been used in nuclear power plants, medical buildings for radiation therapy, nuclear research facilities, and storage of radioactive waste. Compared with radiation-proof materials such as steel plates and lead plates, radiation-proof concrete has a series of advantages such as high technical and economic benefits, good structural characteristics, and excellent radiation shielding effects. At present, there are two main technologies for large-volume radiation-proof concrete: one is to select high-density aggregates such as magnetite, limonite or barite to increase the apparent density of concrete and use the material properties to shield radiation. However, such coarse aggregates have a large self-weight and slightly low strength, which makes the concrete easy to stratify and segregate, and has poor mechanical properties; the second is to use high-performance concrete to improve the density and crack prevention level of concrete, but because no high apparent density materials are selected, it mainly relies on increasing the thickness of the concrete slab to shield radiation. Due to the increase in the volume of the structure, the internal temperature of the concrete increases during the construction process, which is prone to temperature cracks. Moreover, most radiation-proof concrete is in a high-temperature environment, which is easy to cause the concrete to crack during operation, which will directly reduce the radiation shielding ability of the concrete.
[0004] At present, the common problem is that most of the prepared radiation-proof concrete is based on high-density aggregates such as barite, the concrete structure is heavy, the concrete is easy to stratify and segregate, and the radiation protection effect is average. Therefore, it is urgent to develop a radiation-proof aggregate that can improve the radiation resistance of concrete while reducing the weight of the aggregate, solve the problem of easy segregation and stratification of concrete, and improve the working performance and mechanical properties of concrete. Summary of the invention
[0005] In view of the deficiencies in the above prior art, one of the objects of the present invention is to provide a method for preparing a radiation-proof aggregate. The radiation-proof aggregate prepared by the present invention can attenuate the radiation energy gradient and has excellent deceleration, weakening and absorption effects on radiation rays. In addition, the radiation-proof aggregate prepared by the present invention has the characteristics of relatively small apparent density and high strength, which can avoid segregation and stratification of concrete and improve the working and mechanical properties of concrete.
[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0007] A method for preparing a radiation-proof aggregate comprises the following steps:
[0008] S1. After the lead powder, iron ore powder and barium cement are mixed evenly, hydrogen peroxide and water are added, mixed evenly and granulated, and the wet particles are steam cured and heated at high temperature to obtain the aggregate core;
[0009] S2. The aggregate core obtained in step S1 is immersed in a mixed solution of sodium alginate and boron fiber, and then the aggregate core is sprayed with an aqueous solution of calcium chloride to obtain aggregate particles;
[0010] S3. The red mud and graphite powder are mixed evenly and calcined at 800-900° C. The powder is obtained by grinding and sieving. The powder is mixed evenly with an alkaline activator and water is added to obtain a slurry. The slurry is then mixed with the aggregate particles obtained in step S2. The aggregate is formed and then cured to obtain the radiation-proof aggregate.
[0011] Lead (Pb) powder is a high-density material with excellent deceleration, refraction and absorption capabilities for gamma rays; iron ore powder contains a large amount of iron oxide, which has good absorption capacity for gamma rays and strong elastic scattering ability for neutron radiation (can be used to scatter and dissipate neutron radiation that penetrates the middle layer of aggregate), and can also improve the strength of the core aggregate; the barium ions in barium cement have good radiation protection capabilities, and barium cement forms a bonding adhesive with water to bond lead powder and iron ore powder, further improving the strength of the core aggregate and providing an alkaline environment. Hydrogen peroxide will decompose in an alkaline environment to produce oxygen (O2) gas. The gas is connected and steamed to set the shape, and then evaporated at high temperature to form a pore structure inside the aggregate. The pore distribution is random and irregular, which can effectively reduce the dead weight of the aggregate and reduce the segregation of radiation-proof concrete. The present invention uses lead powder, iron powder and barium cement to prepare a high-density aggregate core with irregular channels. When the rays enter the concrete, low, medium and part of high-energy radiation rays can be absorbed by other auxiliary materials or aggregate layers, and higher-energy gamma and neutron rays enter the interior of the aggregate. The irregular channels with a certain degree of roughness cause the rays to be reflected in different directions. On the one hand, the path length of the radiation inside the aggregate is extended, and the energy attenuation of the rays is increased. On the other hand, the radiation is reflected and refracted multiple times at different angles and surfaces, and each reflection reduces the energy, which eventually causes the energy of the rays to be gradually reduced, and finally the rays are absorbed and cannot smoothly penetrate the aggregate.
[0012] Sodium alginate itself is very rich in hydrogen. Each carbon atom in its molecule is connected to several hydrogen atoms. In addition to the main chain of the sugar molecule, there are many hydroxyl groups (-OH). At the same time, sodium alginate has good water absorption and gelation properties. It reacts with calcium ions to form gel and retain moisture. Based on the rich hydrogen elements in sodium alginate itself and the H element in the absorbed water, the mass of hydrogen nuclei and neutrons is equal. When the two collide, the neutron speed is greatly reduced, and the fast neutrons are converted into thermal neutrons. At the same time, the B element in the boron fiber is introduced, which can capture thermal neutrons, absorb neutrons and convert them into other particles, thereby effectively reducing and absorbing neutron radiation energy. The middle structural layer of the aggregate plays the role of bonding the upper and lower layers of the aggregate, buffering stress and curing. Sodium alginate solution reacts with calcium chloride to form calcium alginate gel, whose three-dimensional network structure has a certain bonding and strengthening effect. At the same time, the boron fiber is distributed in the gel and can be inserted into the inner core layer of the radiation-proof aggregate (the gel penetrates into the pores of the inner core layer, and the fiber is inserted into the inner core layer) and the outer layer structure, playing the role of interlocking connection between the upper, middle and lower layers, effectively improving the interlayer connection and aggregate strength of the aggregate structure. At the same time, calcium alginate gel has a certain flexibility and elasticity, which can help the inner and outer layers to disperse stress and reduce the shrinkage stress of the inner and outer layers, which may cause the aggregate to rupture or deform. In addition, sodium alginate gel can slowly release water through the gel network structure in the later stage, improve the hydration of the inner core layer barium cement and the outer layer geopolymer, and effectively improve the overall strength of the aggregate.
[0013] Red mud contains relatively rich silicon dioxide, aluminum oxide and iron oxide. During the high-temperature calcination process, graphite is added as a reducing agent to react with the iron oxide in the red mud, reduce the iron ions in the iron oxide, produce metallic iron, and enhance the blocking effect of the outer layer of the aggregate on radiation rays. At the same time, a part of the graphite is retained in the calcined red mud. The layered and crystal structure of graphite enables it to effectively absorb and scatter radiation, especially gamma rays and neutron rays, which can slow down their penetration depth. The activity of red mud after high-temperature calcination is significantly improved. It is reacted with an alkali activator to prepare a geopolymer cementitious material, forming the outermost coating layer of the aggregate, improving the density and strength of the aggregate. At the same time, when the aggregate is added to the concrete, the alkali activator in the outermost layer of the aggregate can also play an exciting role, effectively strengthening the transition zone between the radiation-proof aggregate and the cement-based interface, and improving the overall density and mechanical properties of the concrete.
[0014] Preferably, in step S1, the mass ratio of the lead powder, iron ore powder and barium cement is (70-75):(5-10):(10-15).
[0015] Preferably, the mass of the hydrogen peroxide is 3% to 5% of the total mass of the lead powder, iron ore powder and barium cement.
[0016] Preferably, in step S1, the high temperature heating is performed at a temperature of 200-300° C. and a time of 20-40 min.
[0017] Preferably, in step S2, in the mixed solution, the mass ratio of sodium alginate, water and boron fiber is (1-2):30:2.
[0018] Preferably, in step S2, the boron fiber has a boron content of 35%-40%, a length of 2-3 mm, a diameter of 5-10 μm, and a tensile modulus of 300-400 GPa.
[0019] Preferably, in step S3, the mass ratio of red mud to graphite powder is 10:(0.5~2).
[0020] Preferably, in step S3, the mass of the alkaline active agent is 7% to 8% of the mass of the powder.
[0021] Preferably, the alkaline activator comprises Na2SiO3 and NaOH.
[0022] Another object of the present invention is to provide a radiation-proof aggregate prepared by the preparation method, wherein the apparent density of the radiation-proof aggregate is 2800-3000 kg / m³.
[0023] Aiming at the problem that most of the radiation-proof concrete in the prior art is based on high-density aggregates such as barite, the concrete structure has a large deadweight, the radiation protection effect is general, and the shielding performance, working and mechanical properties, and crack resistance cannot be taken into account, another object of the present invention is to provide a high-strength, crack-resistant, radiation-proof concrete made of the radiation-proof aggregate, comprising the following components in parts by weight: 300-350 parts of cement, 50-60 parts of fly ash, 40-50 parts of lithium slag powder, 500-600 parts of sand, 150-200 parts of xenotime sand, 220-260 parts of radiation-proof aggregate, 810-850 parts of crushed stone, 2-4 parts of brucite composite fiber, 6-9 parts of water reducer, and 155-170 parts of water; the brucite composite fiber is obtained by melting, extruding, and spinning brucite fiber, polyethylene, and nano-tungsten oxide.
[0024] The present invention adopts lithium slag powder, yttrium phosphate ore sand, and radiation-proof aggregate to form a multi-level radiation energy attenuation protection system, and cooperates with brucite composite fiber to strengthen the radiation protection and crack resistance and toughening effect, comprehensively improves the radiation protection performance of concrete, and takes into account the work, mechanics and crack resistance performance, which can effectively improve the safety of radiation protection engineering structures and extend their service life.
[0025] Lithium slag contains relatively rich lithium oxide and silicon dioxide. When lithium slag is added to concrete, the silicate component can react with calcium hydroxide to generate more hydrated calcium silicate, thereby improving the compactness and strength of concrete. Lithium slag contains lithium (Li). When the isotope of lithium (Li-6) reacts with neutrons, it can absorb neutrons and convert into tritium (T) and helium-4 (He-4), which absorbs neutron rays. Lithium slag has a porous structure and is easy to absorb water. When added to concrete as an admixture, it absorbs water and stores it. On the one hand, it plays an effect of internal curing to enhance the strength of concrete. On the other hand, the pore structure formed in the cement-based material can increase the total water content of concrete to a certain extent. The hydrogen atoms in the water can collide with neutrons, which can effectively slow down the neutron speed.
[0026] The cement-based mortar formed by yttrium phosphate sand wraps the coarse aggregate and fills the pores. The high density of yttrium phosphate can increase the density of cement paste, reduce the density difference between radiation-proof aggregate and cement paste, and reduce the segregation rate of concrete mixture. At the same time, the phosphate minerals rich in yttrium phosphate can react with calcium hydroxide in concrete to form calcium phosphate minerals, which can enhance the cohesion and strength of concrete. Yttrium phosphate is rich in yttrium (Y, atomic number 39) and rare earth elements such as cerium and lanthanum. The nuclei of these high atomic number elements can effectively weaken the radiation intensity of gamma rays and X-rays through Compton scattering and photoelectric effect, and the rare earth oxides in yttrium phosphate can absorb part of the neutron energy through nuclear reactions and deceleration of neutrons, thereby reducing its penetration.
[0027] The brucite composite fiber prepared by the present invention using brucite fiber, polyethylene and nano tungsten oxide has high strength, toughness, crack resistance, water dispersibility and radiation resistance, and can effectively improve the mechanical and crack resistance and radiation resistance of concrete. The brucite fiber has good strength, water dispersibility and alkali resistance, and has good compatibility with cement-based materials. At the same time, the brucite fiber has a high hydrogen content, which can further improve the neutron radiation resistance of concrete; polyethylene (PE) has good toughness and ductility, which can improve the toughness and fracture resistance of the composite fiber, supplement the brittleness of the brucite fiber, and enhance the overall ductility and fatigue resistance of the composite fiber. At the same time, the molecular structure of polyethylene is mainly composed of CH bonds, which has a high hydrogen content, and can further supplement the hydrogen element in the composite fiber; tungsten oxide has a high electronic band gap. When irradiated, the generation of electron and hole pairs and their migration in the material help to disperse and slow down the energy transfer of radiation. At the same time, the ultra-high surface area, surface energy and density of nano tungsten oxide are used to increase the interface with the radiation rays, and the efficient absorption of radiation is achieved through the photoelectric effect and Compton scattering.
[0028] Preferably, the brucite composite fiber has a diameter of 40-50 μm, a length of 15-25 mm, a tensile strength of 320-350 MPa, and a Young's modulus of 2.5 GPa-2.7 GPa.
[0029] Preferably, the preparation method of the brucite composite fiber is as follows: pre-treating the nano tungsten oxide with a silane coupling agent and setting aside; heating polyethylene particles to a molten state, then adding brucite fiber and the pre-treated nano tungsten oxide, mixing evenly, extruding, spinning, and cooling to obtain the brucite composite fiber.
[0030] More preferably, the mass ratio of the brucite fiber, polyethylene and nano-tungsten oxide is (50-70): (35-45); (15-25).
[0031] Compared with the prior art, the present invention is beneficial in that:
[0032] (1) The radiation-proof aggregate prepared by the present invention has a three-layer structure, which can form a hierarchical attenuation of radiation energy and finally absorb radiation energy. The inner core of the aggregate has irregular channels, which can make the high-energy gamma and neutron rays that eventually enter the aggregate reflect in different directions, extend the path, attenuate the energy, and finally absorb radiation. The middle layer is based on the rich hydrogen element of sodium alginate itself and the H element of the absorbed water. At the same time, boron fiber is introduced to reduce the absorption of neutron radiation energy, and play the role of bonding the upper and lower layers of the aggregate, buffering stress and curing; the outermost layer is wrapped with red mud geopolymer. The metallic iron produced by the calcination and reduction of red mud and the graphite added in the process improve the outermost layer's weakening and absorption of radiation rays, while improving the density and strength of the aggregate and strengthening the transition zone between the aggregate and the cement-based interface.
[0033] (2) The present invention uses lithium slag to improve the compactness and strength of concrete, and achieves the effect of internal curing. At the same time, the lithium slag itself and the pore structure formed in the concrete with increased water content can both slow down neutron rays. Xenotime ore sand reduces the segregation rate of the mixture of radiation-proof aggregate concrete, enhances the cohesion, density and strength of the concrete. At the same time, xenotime ore is rich in rare earth elements such as yttrium and cerium, which can weaken the intensity of γ radiation and slow down neutrons. Brucite composite fiber has a series of characteristics such as high strength, toughness, and radiation resistance. While improving the mechanical and crack resistance of concrete, it is cross-distributed in the concrete to further improve the radiation protection performance.
[0034] (3) In the present invention, radiation protection is designed for cementitious materials, sand materials and aggregates. Lithium slag powder, yttrium phosphate sand and radiation-proof aggregates are used to form a multi-level radiation energy attenuation protection system. At the same time, brucite composite fiber is used to enhance the radiation protection and crack resistance and toughening effect. The radiation protection performance of concrete is comprehensively improved while taking into account the work, mechanical and crack resistance performance. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The method for preparing the radiation-proof aggregate of the present invention comprises the following steps:
[0037] S1. After the lead powder, iron ore powder and barium cement are mixed evenly, hydrogen peroxide and water are added, mixed evenly and granulated, and the wet particles are steam cured and heated at high temperature to obtain the aggregate core;
[0038] S2. The aggregate core obtained in step S1 is immersed in a mixed solution of sodium alginate and boron fiber, and then the aggregate core is sprayed with an aqueous solution of calcium chloride to obtain aggregate particles;
[0039] S3. The red mud and graphite powder are mixed evenly and calcined at 800-900° C. The powder is obtained by grinding and sieving. The powder is mixed evenly with an alkaline activator and water is added to obtain a slurry. The slurry is then mixed with the aggregate particles obtained in step S2. The aggregate is formed and then cured to obtain the radiation-proof aggregate.
[0040] In the embodiments and comparative examples of the present invention, the particle size of the lead powder is 20-45 μm, and the lead content is ≥99%; the iron content of the iron ore powder is ≥70%, and the specific surface area is 2000-2500 cm 2 / g; the density of barium cement is 3.5~3.7g / cm 3 , barium sulfate content ≥90%; boron content in boron fiber is 35%-40%, length is 2-3mm, diameter is 5-10μm, tensile modulus is 300-400GPa; red mud contains SiO2≥20%, Fe2O3≥30%, Al2O3≥20%, TiO2≥5%; brucite fiber, produced by Jihong Mineral Products Processing Plant, Lingshou County, Hebei Province, with tensile strength of 892.4~1283.7MPa; silane coupling agent KH570, produced by Guangzhou Yihuisheng Chemical Co., Ltd.; nano tungsten oxide particle size is 40~50nm, produced by Shanghai Pantian Powder Material Co., Ltd.; polyethylene particles have a particle size of 35~50μm, produced by Taixing Chunfen Plastic Products Co., Ltd.
[0041] The high-strength crack-resistant radiation-proof concrete of the invention comprises the following components in parts by weight: 300-350 parts of cement, 50-60 parts of fly ash, 40-50 parts of lithium slag powder, 500-600 parts of sand, 150-200 parts of xenotime sand, 220-260 parts of radiation-proof aggregate, 810-850 parts of crushed stone, 2-4 parts of brucite composite fiber, 6-9 parts of water reducer and 155-170 parts of water; the brucite composite fiber is obtained by melting, extruding and spinning brucite fiber, polyethylene and nano-tungsten oxide.
[0042] The cement is ordinary Portland cement P•O 42.5; the fly ash is Class I fly ash; the specific surface area of the lithium slag is 400~500m 2 / kg; the fineness modulus of natural sand is 2.8~3.2; the fineness modulus of xenotime sand is 1.4~2.5; the water reducer is polycarboxylate water reducer with a water reduction rate of 35% and a solid content of 37%.
[0043] Example 1
[0044] This embodiment provides a method for preparing radiation-proof aggregate, comprising the following steps:
[0045] S1. Mix lead powder, iron ore powder and barium cement in a mass ratio of 70:10:15 to obtain a mixed powder, add 5% of hydrogen peroxide and 15% of water to the mixed powder, mix well, and granulate to prepare spherical wet particles with a particle size of 2-8 mm; then steam cure the wet particles at 80°C for 10 hours, then heat at 200°C for 30 minutes, take out and cool to room temperature to obtain an aggregate core;
[0046] S2. The aggregate core obtained in step S1 is placed in a mixed solution of sodium alginate and boron fiber and soaked for 30 minutes, wherein the mass ratio of sodium alginate, water and boron fiber in the mixed solution is 2:30:2, and then taken out and sprayed with a 0.5wt% calcium chloride solution, wherein the mass ratio of the calcium chloride solution to the aggregate core is 100:1, and then allowed to stand at room temperature for 30 minutes to obtain aggregate particles with a particle size of 3 to 10 mm;
[0047] S3. Mix red mud and graphite powder in a mass ratio of 10:1, calcine in a high-temperature furnace at 900°C for 100 minutes, grind into a uniform powder with a particle size of less than 75μm after cooling, and then mix the powder with an alkaline activator of 8% by mass of the powder, add water of 40% by mass of the powder, and stir to obtain a slurry, wherein the alkaline activator is composed of NaOH and Na2SiO3 in a mass ratio of 1:5; then mix the slurry with the aggregate particles obtained in step S2, use a pelletizing machine to shape the aggregate, let it stand for 1 day, and then cure it under a standard curing environment for 7 days to obtain a radiation-proof aggregate with a particle size of 5-20mm.
[0048] Example 2
[0049] This embodiment provides a method for preparing radiation-proof aggregate, comprising the following steps:
[0050] S1. Mix lead powder, iron ore powder and barium cement in a mass ratio of 75:5:10 to obtain a mixed powder, add 3% of hydrogen peroxide and 10% of water to the mixed powder, mix well, and granulate to prepare spherical wet particles with a particle size of 2-8 mm; then steam cure the wet particles at 90°C for 8 hours, then heat them at 300°C for 20 minutes, take them out and cool them to room temperature to obtain the aggregate core;
[0051] S2. The aggregate core obtained in step S1 is placed in a mixed solution of sodium alginate and boron fiber and soaked for 20 minutes, wherein the mass ratio of sodium alginate, water and boron fiber in the mixed solution is 1:30:2, and then taken out and sprayed with a 1.0wt% calcium chloride solution, wherein the mass ratio of the calcium chloride solution to the aggregate core is 80:1, and then allowed to stand at room temperature for 20 minutes to obtain aggregate particles with a particle size of 3 to 10 mm;
[0052] S3. Red mud and graphite powder are mixed evenly in a mass ratio of 10:2, calcined in a high-temperature furnace at 800°C for 120 minutes, and ground into uniform powder with a particle size of less than 75 μm after cooling, and then the powder is mixed evenly with an alkaline activator of 7% by mass of the powder, and water of 38% by mass of the powder is added, and the slurry is obtained after being stirred evenly, wherein the alkaline activator is composed of NaOH and Na2SiO3 in a mass ratio of 1:6; and then the slurry is mixed with the aggregate particles obtained in step S2, and the aggregate is formed by a pelletizing machine. After standing for 1 day, it is cured for 4 days under a standard curing environment to obtain a radiation-proof aggregate with a particle size of 5-20 mm.
[0053] Comparative Example 1
[0054] The preparation method of the radiation-proof aggregate in this comparative example is basically the same as that in Example 1, except that step S1 is as follows: lead powder, iron ore powder and barium cement are mixed uniformly in a mass ratio of 70:10:15 to obtain a mixed powder, 15% water by mass of the mixed powder is added, the mixture is mixed uniformly, and granulation is performed to prepare spherical wet particles with a particle size of 2-8 mm; the wet particles are then steam-cured at 80° C. for 10 h to obtain an aggregate core.
[0055] Comparative Example 2
[0056] The preparation method of the radiation-proof aggregate in this comparative example is basically the same as that in Example 1, except that a corresponding weight of boron powder is used to replace the boron fiber in step S2.
[0057] Comparative Example 3
[0058] The preparation method of the radiation-proof aggregate in this comparative example is basically the same as that in Example 1, except that step S3 is as follows: the aggregate particles obtained in step S2 are mixed with cement slurry, and the aggregate is formed by a pelletizing machine. After standing for 1 day, the aggregate is cured for 7 days under a standard curing environment to obtain a radiation-proof aggregate with a particle size of 5-20 mm.
[0059] With reference to GB / T 14685-2022 "Pebble and Crushed Stone for Construction", the crushing value and apparent density of the radiation protection aggregates of Examples 1-2 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1.
[0060]
[0061] From the test results in Table 1, it can be seen that the crushing values of the radiation protection aggregates of Example 1 and Example 2 are around 6.0%~6.2%, the crushing values are generally low, and the compressive strength of the aggregates is excellent. The apparent densities are 2880kg / m 3 and 2910kg / m 3 , much lower than traditional barite (4300-4600 kg / m 3) and the apparent density of magnetite aggregate (5000-5300 kg / m 3 In the aggregate preparation process of Comparative Example 1, no hydrogen peroxide was added in step S1, and no high-temperature heating was performed. No irregular pore structure was formed inside the aggregate. Although the compressive strength of the aggregate was improved, the final apparent density was 3480 kg / m 3 , much higher than Example 1. The aggregate density is relatively large, and the mixed concrete is prone to segregation, which affects the workability and mechanical properties of the concrete. Comparative Example 2 uses a corresponding weight of boron powder to replace the boron fiber. Compared with Example 1, its crushing value is increased by 14.5%, and the aggregate strength is reduced. This is because the boron powder is distributed in the sodium alginate gel, and cannot provide interlayer connection for the upper and lower layers of the aggregate, thereby enhancing the aggregate strength. This also shows that the boron fiber is distributed in the gel and can be inserted into the inner and outer layer structures of the radiation-proof aggregate, playing the role of interlocking connection of the upper, middle and lower layers, effectively improving the interlayer connection and aggregate strength of the aggregate structure.
[0062] Example 3
[0063] The present embodiment provides a high-strength, crack-resistant and radiation-proof concrete, comprising the following components in parts by weight: 350 parts of cement, 60 parts of fly ash, 40 parts of lithium slag powder, 600 parts of natural sand, 150 parts of xenotime sand, 220 parts of the radiation-proof aggregate prepared in Example 1, 810 parts of crushed stone, 4 parts of brucite composite fiber, 9 parts of water reducer, and 170 parts of water.
[0064] The preparation method of brucite composite fiber is as follows: (1) brucite fiber, polyethylene particles and nano tungsten oxide are weighed in a mass ratio of 60:40:20, and the nano tungsten oxide is treated with a silane coupling agent KH570 and set aside; the polyethylene particles are heated to a molten state and the temperature is maintained at 190-200°C. (2) Then the brucite fiber and nano tungsten oxide are added to the molten polyethylene, and a twin-screw extruder is used to uniformly mix them at 200-300 rpm, and the mixed molten material is pushed out of the extruder, and the outlet pressure of the extruder is 18-20 MPa. The fiber is stretched into a fiber with a diameter of 40-50 μm using a spinning technology, and the fiber temperature is lowered by a cooling water tank to solidify and shape it, and then sheared to a length of 15-25 mm to obtain brucite composite fiber.
[0065] The preparation method of the high-strength crack-resistant radiation-proof concrete of this embodiment comprises the following steps:
[0066] M1. Weigh each component by weight;
[0067] M2. Dry mix radiation-proof aggregate, crushed stone, xenotime sand, natural sand, cement and fly ash for 10-15 seconds, then add 1 / 2 water reducer and 1 / 2 water, mix for 40-60 seconds, then add lithium slag powder, brucite composite fiber, the remaining 1 / 2 water reducer and 1 / 2 water, mix evenly for 40-60 seconds to obtain concrete slurry.
[0068] In step M2, 1 / 2 water reducing agent refers to 1 / 2 of the total amount of water reducing agent, and 1 / 2 water refers to 1 / 2 of the total amount of water.
[0069] Example 4
[0070] The high-strength, crack-resistant and radiation-proof concrete of Example 4 is basically the same as that of Example 3, except that it includes the following components in parts by weight: 300 parts of cement, 50 parts of fly ash, 50 parts of lithium slag powder, 550 parts of natural sand, 200 parts of xenotime sand, 260 parts of the radiation-proof aggregate prepared in Example 1, 850 parts of crushed stone, 2 parts of brucite composite fiber, 6 parts of water reducer, and 155 parts of water.
[0071] Example 5
[0072] The difference between Example 5 and Example 3 is that the radiation-resistant aggregate of Example 2 is used instead of the radiation-resistant aggregate of Example 1.
[0073] Comparative Example 4
[0074] The difference between Comparative Example 4 and Example 3 is that the radiation-resistant aggregate of Comparative Example 1 is used instead of the radiation-resistant aggregate of Example 1.
[0075] Comparative Example 5
[0076] The difference between Comparative Example 5 and Example 3 is that the radiation-resistant aggregate of Comparative Example 2 is used instead of the radiation-resistant aggregate of Example 1.
[0077] Comparative Example 6
[0078] The difference between Comparative Example 6 and Example 3 is that the radiation-resistant aggregate of Comparative Example 3 is used instead of the radiation-resistant aggregate of Example 1.
[0079] Comparative Example 7
[0080] The difference between Comparative Example 7 and Example 3 is that an equal amount of slag powder is used to replace lithium slag powder.
[0081] Comparative Example 8
[0082] The difference between Comparative Example 8 and Example 3 is that an equal amount of brucite fibers is used to replace the brucite composite fibers.
[0083] The working performance, mechanical properties, crack resistance and radiation protection performance of the high-strength crack-resistant and radiation-proof concrete of Examples 3 to 5 and Comparative Examples 4 to 8 were tested. The test results are shown in Table 2.
[0084] According to the provisions of GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the working performance of the freshly mixed concrete of the examples and comparative examples was tested. The larger the slump, the better the fluidity; the mechanical properties of the concrete were tested according to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Ordinary Concrete"; and the early crack resistance and impermeability of the concrete were tested according to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The "anti-crack plate test" was used to determine the early crack resistance of concrete. The test results were expressed as the total crack area per unit area calculated. The smaller the value, the better the crack resistance.
[0085] According to GB 18871-2002 "Basic Standard for Ionizing Radiation Protection and Radiation Source Safety", the radiation protection performance of concrete is tested. The linear attenuation coefficient of concrete gamma rays and neutron rays (cm -1 ), the larger the linear attenuation coefficient, the better the radiation protection performance of the concrete; γ-ray measurement equipment: nuclear radiation detector; neutron ray measurement equipment: neutron source; irradiation energy 4MeV.
[0086]
[0087] From the test results in Table 2, it can be seen that in terms of working performance, the slump of the embodiments is greater than or equal to 200 mm, and has high flowability. At the same time, the cement paste and aggregate in the concrete are tightly wrapped, with good cohesion and no segregation, which can ensure better construction pumpability. The radiation-proof aggregate used in Comparative Example 4 is the same as that in Comparative Example 1. Because the aggregate density is relatively large at 3480 kg / m 3 The slump of the concrete is 180mm, the fluidity is reduced, and segregation occurs.
[0088] In terms of mechanical properties and crack resistance, the 28d compressive strength of Examples 3 to 5 is generally between 56.8MPa and 57.6MPa, and the total cracking area per unit area is 30-35mm. 2 / m 2, excellent crack resistance; the flowability of comparative example 4 is reduced and segregation occurs, resulting in reduced compressive strength and crack resistance of its hardened concrete; the crushing value of the radiation-proof aggregate in comparative example 5 increases, and the compressive strength of the concrete decreases; compared with Example 3, the outermost layer of the radiation-proof aggregate used in comparative example 6 is cement, because there is no alkali-activated material, the transition zone between the aggregate and the cement base is not effectively enhanced, and the concrete strength is slightly reduced. Although the volcanic ash activity of the slag powder in comparative example 7 is higher than that of lithium slag, lithium slag has a certain internal curing effect, so the compressive strength of the concrete of the two is not much different, and the excessive volcanic ash activity will also increase the hydration heat of the concrete, affecting the crack resistance; ordinary brucite fiber is used in comparative example 8, and its fiber toughness is relatively insufficient, and its concrete crack resistance is worse than that of Example 3.
[0089] In terms of radiation protection performance, the linear attenuation coefficients of gamma rays and neutron rays of Examples 3 to 5 are 0.72-0.76 cm -1 、0.60-0.64cm -1 Compared with Example 3, the radiation-proof aggregate of Comparative Example 4 is more dense, but the concrete shows segregation, the compactness is reduced, and the overall radiation-proof performance of the concrete is attenuated; the linear attenuation coefficient of γ-rays and the linear attenuation coefficient of neutron rays in Comparative Example 5 are 0.60 cm -1 、0.52cm -1 , mainly because the density and strength of the interlayer of the radiation-proof aggregate are reduced, and the radiation-proof performance of the concrete is correspondingly reduced; the outermost layer of the radiation-proof aggregate used in Comparative Example 6 is cement paste, and compared with Example 3, the aggregate does not contain iron oxide and graphite anti-γ-ray radiation material components, and the γ-ray linear attenuation coefficient of its concrete is reduced, and the neutron ray linear attenuation coefficient does not show a significant decrease; the neutron ray linear attenuation coefficient of Comparative Example 7 is reduced by 20% compared with Example 3, which shows that lithium slag added to concrete can effectively slow down and absorb neutron rays; the test results of Comparative Example 8 prove that the brucite composite fiber has an improvement effect on the crack resistance of concrete, the concrete tends to be denser, and the radiation protection performance is better. At the same time, the ability of the brucite fiber itself to resist γ-rays and neutron rays has a significant improvement effect on the radiation protection performance of concrete.
[0090] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing radiation-proof aggregate, characterized in that: The following steps are involved: S1. After the lead powder, iron ore powder and barium cement are mixed evenly, hydrogen peroxide and water are added, mixed evenly and granulated, and the wet particles are steam cured and heated at high temperature to obtain the aggregate core; S2. The aggregate core obtained in step S1 is immersed in a mixed solution of sodium alginate and boron fiber, and then the aggregate core is sprayed with an aqueous solution of calcium chloride to obtain aggregate particles; S3. The red mud and graphite powder are mixed evenly and calcined at 800-900° C. The powder is obtained by grinding and sieving. The powder is mixed evenly with an alkaline activator and water is added to obtain a slurry. The slurry is then mixed with the aggregate particles obtained in step S2. The aggregate is formed and then cured to obtain the radiation-proof aggregate.
2. The method for preparing a radiation-proof aggregate according to claim 1, characterized in that: In step S1, the mass ratio of the lead powder, the iron ore powder and the barium cement is (70-75): (5-10): (10-15).
3. The method for preparing a radiation-proof aggregate according to claim 1, characterized in that: The mass of the hydrogen peroxide is 3% to 5% of the total mass of the lead powder, the iron ore powder and the barium cement.
4. The method for preparing a radiation-proof aggregate according to claim 1, characterized in that: In step S1, the high temperature heating temperature is 200-300°C and the time is 20-40 minutes.
5. The method for preparing a radiation-proof aggregate according to claim 1, characterized in that: In step S2, in the mixed solution, the mass ratio of sodium alginate, water and boron fiber is (1-2):30:
2.
6. The method for preparing a radiation-proof aggregate according to claim 1, characterized in that: In step S3, the mass ratio of the red mud to the graphite powder is 10:(0.5-2).
7. The radiation-proof aggregate prepared by the preparation method according to any one of claims 1 to 6.
8. A high-strength, crack-resistant and radiation-proof concrete made of the radiation-proof aggregate prepared by the method according to any one of claims 1 to 6, characterized in that: The invention comprises the following components in parts by weight: 300-350 parts of cement, 50-60 parts of fly ash, 40-50 parts of lithium slag powder, 500-600 parts of sand, 150-200 parts of xenotime sand, 220-260 parts of radiation-proof aggregate, 810-850 parts of crushed stone, 2-4 parts of brucite composite fiber, 6-9 parts of water reducer and 155-170 parts of water; The brucite composite fiber is obtained by melting, extruding and spinning brucite fiber, polyethylene and nano-tungsten oxide.
9. The high-strength crack-resistant and radiation-proof concrete according to claim 8, characterized in that: The preparation method of the brucite composite fiber is as follows: pre-treating nano tungsten oxide with a silane coupling agent and setting aside; heating polyethylene particles to a molten state, then adding brucite fiber and the pre-treated nano tungsten oxide, mixing evenly, extruding, spinning, and cooling to obtain the brucite composite fiber.
10. The high-strength crack-resistant and radiation-proof concrete according to claim 9, characterized in that: The mass ratio of the brucite fiber, polyethylene and nano-tungsten oxide is (50-70): (35-45); (15-25).
Citation Information
Patent Citations
Anti-radiation concrete and preparation method thereof
CN112010593A
Boron-containing barite radiation protection concrete and preparation method thereof
CN114835452A
Highly dense red mud shield for x-and gamma-ray attenuation
CN116194418A
Synthetic Additive Materials for Concretes or Building Elements for Protection Against Ionizing Radiations
GB1185893A
Concrete composition and concrete cured body
JP2018012616A
Cited By
High-energy-radiation-resistant ethylene propylene diene monomer and preparation method thereof
CN121136289A